On the Relationship between Prayer and Moral Virtues in the Quran and Mysticism - amrollah moin (پژوهش نامه معارف قرآنی, 2013)
Since the dawn of creation, in both divine and non-divine religions, the believers have resorted to worship and above all prayer to express their gratitude to their God or gods. It is no exaggeration to deem prayer the gist of servitude as sincere prayer embraces all elements of unshakable faith. This article seeks to study the extent to which a sincere prayer- sayer gains access to moral virtues and the prayer speeds up his moral growth and the impact the moral growth has on the content of the prayer. As a spiritual practice, prayer encourages the prayer-sayer to challenge his ego.